Morals and Manners Education for Children Aged 7-12 Years at TPQ Masjid An Nahl Ciangsana Bogor - Efendi, Yudi; Rahman, Imas Kania; Supraha, Wido; Andriana, Nesia (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2025)
Islamic Education involves a deliberate and structured approach that aims to equip students with the ability to recognize, understand, appreciate, believe, commit, and embody noble behaviors in accordance with the Qur'an and Hadith. Children are a gift from Allah Swt. and their essence is priceless to those who educate them. When positive values are nurtured since young age, they will develop into good individuals and find happiness both in this world and the hereafter. This research seeks to explore aspects of morals and manners education for children aged 7 to 12 years. This research was conducted by looking at the practice of morals and manners education from various previous research literature, as well as in the context of the TPQ Masjid An Nahl Ciangsana Bogor. Using a qualitative research approach that emphasizes descriptive analysis, this study collected data through literature review and field research, including interviews. The findings show that moral education is very important especially for children of tamyiz or before baligh age. By implementing four manners, namely the manners of studying, the manners of worship in the mosque, the manners of eating and drinking and the manners of making friends, it is hoped that the students will become pious and have good morals.Pendidikan Agama Islam adalah upaya sadar dan terencana dalam menyiapkan peserta didik untuk mengenal, memahami, menghayati, mengimani, bertaqwa, dan berakhlak mulia dalam mengamalkan ajaran agama Islam melalui kegiatan bimbingan, pengajaran, latihan, serta penggunaan pengalaman. Anak adalah anugerah dari Allah Swt. yang tak ternilai harganya bagi mereka yang mendidiknya. Ketika nilai-nilai positif dipupuk dalam diri mereka sejak dini, mereka akan tumbuh menjadi individu yang baik dan menemukan kebahagiaan baik di dunia maupun di akhirat. Penelitian ini berusaha menggali aspek-aspek pendidikan moral dan budi pekerti bagi anak usia 7 hingga 12 tahun. Penelitian ini dilakukan dengan melihat praktik pendidikan akhlak dan adab dari berbagai literatur penelitian terdahulu, serta dalam konteks TPQ Masjid An Nahl Ciangsana Bogor. Dengan menggunakan pendekatan penelitian kualitatif yang menekankan pada analisis deskriptif, penelitian ini mengumpulkan data melalui studi literatur dan penelitian lapangan, termasuk wawancara. Hasil penelitian menunjukkan bahwa pendidikan akhlak sangat penting terutama bagi anak usia tamyiz atau pra baligh. Dengan menerapkan empat adab yaitu adab belajar, adab beribadah di masjid, adab makan dan minum serta adab berteman, diharapkan para santri menjadi anak yang shaleh dan berakhlakul karimah.